A tumor-mitochondria dual targeted aza-BODIPY-based nanotheranostic agent for multimodal imaging-guided phototherapy. Issue 27 (29th June 2018) - Chen, Dapeng; Zhang, Jiaojiao; Tang, Yunyun; Huang, Xiaoyu; Shao, Jinjun; Si, Weili; Ji, Jun; Zhang, Qi; Huang, Wei; Dong, Xiaochen
Abstract : Mitochondria targeted phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has excelled as an effective approach among other non-specific techniques for its high selectivity, non-invasiveness and low systemic toxicity. Abstract : Mitochondria targeted phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has excelled as an effective approach among other non-specific techniques for its high selectivity, non-invasiveness and low systemic toxicity. Derivatives of porphyrins, indocyanine dyes and rhodamine are widely utilized for cancer PDT or PTT. However, limitations, such as hypoxia and heat resistance of PDT and PTT, have restricted their efficacy in tumor treatment, making it urgent to develop highly efficient theranostic agents with synergistic effects. Aza-boron-dipyrromethene (aza-BODIPY) has shown promising prospects for synergistic phototherapy due to its outstanding reactive oxygen species (ROS) generation and photothermal effect. Herein, we designed and synthesized a near-infrared (NIR) aza-BODIPY derivativeMeOABBr ( Φ Δ = 84%). By encapsulating it with polyethylene glycol–folic acid (PEG–FA) and polyethylene glycol–triphenylphosphonium (PEG–TPP), tumor and mitochondria dual targeting nanoparticles (FMAB NPs) have been obtained. Triggered by NIR irradiation, FMAB NPs could generate ROS and hyperthermia ( η = 40%) to cause mitochondrial dysfunction, resulting in cell apoptosis. Simultaneously, FMAB NPs, with unique optical properties, can be monitored precisely by photoacoustic, fluorescence and photothermal imaging in vivo . In particular, as proved by both in vitro and in vivo experiments, tumor-mitochondria dual targetedFMAB NPs exhibit high phototherapeutic efficacy without toxicity to normal tissues.